Ensuring the best interest of the child in adoption process: an overview of the practice in Malaysia - Che Soh @ Yusoff, Roslina; Mohd, Azizah; Abdul Hak, Nora (2013)
Adoption is one of the means to protect children who have been deprived of parental care. The United Nation Convention on Rights of Child guaranteed such protection and as in other action concerning children, the principle of best interest of the child must be primarily considered by the State parties when dealing with the process of adoption. In Malaysia, adoption process is governed under two main legislations, i.e. Adoption Act 1952 and Registration of Adoption Act 1952. However, the principle of best interest of the child is not clearly provided under these two legislations. In addition, inter-country adoption is not in practice in Malaysia. This paper seeks to discuss the extent of the current legislation and practice of the Court in Malaysia in ensuring best interest of the child is guaranteed when dealing with adoption procedure and process. Thus, the relevant laws and decided cases will be examined. The paper also briefly addresses the issue of whether inter-country adoption would be an option for Malaysia and can be a factor in upholding the best interest of children. Finally, the paper discusses some possible recommendations that may spur improvement to the present legislation in ensuring the best interest of the child is duly guaranteed in the adoption process.